The QUASAR reproducibility study, Part II: Results from a multi-center Arterial Spin Labeling test–retest study - Petersen, Esben Thade; Mouridsen, Kim; Golay, Xavier (NeuroImage (Orlando, Fla.), 2010)
Arterial Spin Labeling (ASL) is a method to measure perfusion using magnetically labeled blood water as an endogenous tracer. Being fully non-invasive, this technique is attractive for longitudinal studies of cerebral blood flow in healthy and diseased individuals, or as a surrogate marker of metabolism. So far, ASL has been restricted mostly to specialist centers due to a generally low SNR of the method and potential issues with user-dependent analysis needed to obtain quantitative measurement of cerebral blood flow (CBF). Here, we evaluated a particular implementation of ASL (called Quantitative STAR labeling of Arterial Regions or QUASAR), a method providing user independent quantification of CBF in a large test–retest study across sites from around the world, dubbed “The QUASAR reproducibility study”. Altogether, 28 sites located in Asia, Europe and North America participated and a total of 284 healthy volunteers were scanned. Minimal operator dependence was assured by using an automatic planning tool and its accuracy and potential usefulness in multi-center trials was evaluated as well. Accurate repositioning between sessions was achieved with the automatic planning tool showing mean displacements of 1.87±0.95 mm and rotations of 1.56±0.66°. Mean gray matter CBF was 47.4±7.5 [ml/100 g/min] with a between-subject standard variation SDb=5.5 [ml/100 g/min] and a within-subject standard deviation SDw=4.7 [ml/100 g/min]. The corresponding repeatability was 13.0 [ml/100 g/min] and was found to be within the range of previous studies.